Prevention of biodeterioration of rubberwood(Hevea brasiliensis) using k-otek - Ananthapadmanabha H S; Srinivasan V V (Wood News, 1993)
It is known that rubber wood is highly susceptible to attack by fungi, termites and borers which limits its effective utilisation. In order to increase its durability, boron compounds (boric acid and borax) and sodium pentachlorophenoxide(naPcP) which are water soluble and a combination of CCA (copper sulphate, potassium dichromate and arsenic pentoxide) have so far been recommended as preservatives for enhancing durability against attack by these organisms. It was observed that boron is not fixed in the wood and leaches out slowly when treated wood is exposed outdoors or to continuous moist conditions indoors. Although wood treated with CCA affords better protection against biodeterioration, it has a tendency to leave a greenish colour which is a factor to be considered when the timber is used for furniture. Hence, it was found necessary to find suitable preservatives which can afford reasonable protection and also leaves the natural colour which is one of the necessary prerequisites for manufacturing quality goods. K-Otek, a proprietory chemical with active ingredient `Deltamethrin' - a photostable synthetic pyrethroid and sold with the trade name K-Otek-combi.2.5-50-50-EC, was tested for its insecticidal and fungicidal properties. Rubber wood treated by dip diffusion and pressure treatment (4;solution) gave protection against fungi, borer and termite attack under different environmental conditions for over 10 months. Treated wood also retained its natural colour. Further work on permeability, preservative retention under weathering condition etc, is being continued.
Keywords: Biodeterioration; Rubberwood